A novel TRNSYS type of a coaxial borehole heat exchanger for both short and mid term simulations: B2G model. (5th January 2020) - Cazorla-Marín, Antonio; Montagud-Montalvá, Carla; Tinti, Francesco; Corberán, José Miguel
Highlights: A novel dynamic model of a coaxial borehole heat exchanger is described. An innovative methodology is used to model the local ground with three nodes. Automatic determination of the ground nodes position was addressed. The short and mid-term model behavior was validated against real operation data. Abstract: A dynamic model of a ground source heat pump system is a very useful tool in order to optimize its design and operation. In order to fairly predict the performance of such a system, the dynamic evolution of the fluid entering the heat pump and coming from the borehole heat exchanger (BHE) must be accurately reproduced not only in the long term but also in the short-mid term operating conditions, as it directly affects the coefficient of performance of the heat pump unit. In this context, the B2G model was developed to reproduce the short-term dynamic evolution of the fluid temperature inside the BHE. This work presents the new upgraded version of the B2G dynamic model for a coaxial BHE, which includes several new features to better reproduce not only the short-term but also the mid-term behaviour of the BHE. For that purpose, the model of the surrounding ground has been improved: vertical heat conduction in the grout and ground, heterogenous ground with different layers, and a higher number of ground nodes in the thermal network considered in the model were added, which are automatically located by means of polynomial correlations for any type of ground, geometry and operating conditions. This novel approach has been implemented in TRNSYS for accurately modelling the dynamic behaviour of a coaxial BHE with low computational cost (2.5 s for a 24 h simulation period in a modern computer). The model has been validated against experimental data from a dual source heat pump installation in Tribano (Padua, Italy) and has proven capable of accurately reproducing the short-mid term (up to five days) behaviour of the BHE, with a deviation lower than 0.12 K.